2005
DOI: 10.1002/sita.200400050
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of cardiomyocyte cell cycle: A potential approach for myocardial regeneration

Abstract: Regulation of cardiomyocyte cell cycle appears to be more complex in mammals compared to the lower vertebrates. Cardiomyocytes from the adult newt and zebrafish can proliferate in response to myocardial injury and regenerate the damaged area. In contrast, cardiomyocytes in the mammalian heart cease to proliferate soon after birth. This limits the ability of the mammalian heart to regenerate the damaged myocardium following heart disease. It is believed that increasing the number of myocytes in a diseased heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 176 publications
0
2
0
Order By: Relevance
“…While there is growing body of knowledge on the subject of phenocoversion of fibroblasts to myofibroblasts (12,49), additional studies are required to characterize the mechanisms involved in the regulation of fibroblast proliferation during disease states. Identification of key cell cycle regulators in diseased hearts may serve as effective drug targets to control cardiac fibrosis (1,34,35). A previous study showed that treatment with ISO induced expression of cell cycle proteins and subsequently acinar cell proliferation in rodent salivary glands (61).…”
mentioning
confidence: 98%
“…While there is growing body of knowledge on the subject of phenocoversion of fibroblasts to myofibroblasts (12,49), additional studies are required to characterize the mechanisms involved in the regulation of fibroblast proliferation during disease states. Identification of key cell cycle regulators in diseased hearts may serve as effective drug targets to control cardiac fibrosis (1,34,35). A previous study showed that treatment with ISO induced expression of cell cycle proteins and subsequently acinar cell proliferation in rodent salivary glands (61).…”
mentioning
confidence: 98%
“…[1,2] As a result, myocytes that die in response to several patients. [1,2] As a result, myocytes that die in response to several patients.…”
mentioning
confidence: 99%